IMC plan analysis of three wings of RANGS group RANGS Properties Limited , RANCON autmobiles & RANGS motors - Evan, Riasat Kibria (BRAC University, 2015)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Master of Business Administration, 2015.